3G Handy Guide : Digital Production And Editing - 3G E-LEARNING (New York : 3G E-Learning, 2023)
Digital Production is a new and interdisciplinary field that lies at the cross-section of film production, sound production, design, screenwriting, communication and film theory. It entails transforming creative ideas and assets such as text, images and interactive apps into a variety of digital media, and includes the production of digital music, streaming video, and other widely distributed content. Students learn how to assess and comprehend the media in their environment, create media in a variety of formats, and manage the commercial and technological demands of working in the media industry. Our society has gone digital and virtual in many aspects and it has transformed the way we communicate as a society. Whether it is individual-individual or business-individual conversations, we use a range of digital media such as online advertising, social media, mobile applications and other forms of communication that primarily use technology and Internet to reach out to others. This edition of Handy Guide is thoroughly revised and new topics are added. This Handy Guide prepares students to edit video footage that may be used for commercials, documentaries, television shows and films. Students will be able to write and produce their own work, but will also learn how to participate in a collaborative and creative environment.The theory and practice of various editing styles are covered in order to gain a better understanding of how stories are constructed in the editing room, and how professionals across all fields can leverage the advantages of digital video.Through demonstrations and hands-on experience, students learn advanced editing techniques.Media has changed significantly in the past decade. There are new verticals, new platforms, and new content sources. So how do media experts continue to navigate successfully in this ever-changing space? What are the industry dynamics, and how do you stay on top of the competition?This Handy Guide covers the complete range of production skills necessary for a successful high-definition video produc-tion. Strong emphasis will be placed on proper camera techniques, audio recording techniques, and on creating dynamic and compelling visual compositions